GCMS ANALYSIS ON ANDROGRAPHIS PANICULATA SEED EXTRACT AND ITS ANTICANCER ACTIVITY - S., RAJESWARI; R., VIDYA; P., AMUDHA (International Journal of Applied Pharmaceutics, 2022)
Objective: Andrographis paniculata was an ancient medicinal herb recorded in Ayurvedic system of medicine from long times. The present study is to determine the bioactive phytocomponents present in Andrographis paniculata seed, extraction done using ethanol and Human Liver Cancer (HepG2) cells are used to prove the anticancer activity. Methods: Gas Chromatography-Mass Spectroscopy (GCMS) analysis is used for determining the bioactive constituents of the Andrographis paniculata seed. To prove the in vitro anticancer activity, the MTT assay was done on Human Liver Cancer (HepG2) cells. Results: GCMS analysis of Andrographis paniculata seed extract result determined the presence of 15 active bio components. These various potent bioactive compounds have been proved to possess various pharmacological activities, viz., antimicrobial, antidiabetic, antioxidant, anti-inflammatory and anticancer properties, which were supported by previous findings. The natural compounds with therapeutic effects on traditional medicine have paved the way for evaluating the Andrographis paniculata seeds for cytotoxic activity on HepG2 cell lines. The ethanol extract of Andrographis paniculata seeds was used on HepG2 to evaluate the cytotoxicity; Cisplatin (15 µg/ml) is used as standard with various concentration like 200, 100, 50 and 25 µg/ml were used. The bioactive compounds present in Andrographis paniculata seed extract revealed significant cytotoxicity activity against HepG2 cells with IC50 value of 103.03µg/ml. Conclusion: The cytotoxic effect was found to be concentration-dependent and increased concentration of Andrographis paniculata seed extract showed increased cytotoxicity. The result suggest Andrographis paniculata seed extract have bioactive agents which when treated on hepatocellular carcinoma cells poses excellent anticancer activity.